Legal Uncertainty and Policyholder Protection in Unit-Linked Insurance: A Doctrinal Analysis of Payment Security Under Indonesian Insurance Law - Firdaus Al-Hafiz (Nusantara: Journal of Law and Islamic Law, 2025)
This study examines the legal protection mechanisms available to unit-linked insurance policyholders in Indonesia, specifically focusing on BLife Plan MultiPro products amid payment uncertainties at contract maturity. Using normative-juridical and historical research methods, this doctrinal legal analysis investigates the effectiveness of existing regulatory frameworks in addressing multidimensional uncertainties arising from investment value fluctuations, complex claim procedures, and policy clause interpretations. The theoretical framework integrates Fuller's legal certainty principles with eight internal morality standards, Hart's open texture concept for judicial discretion, and Knight's risk-uncertainty distinction to analyze payment security issues systematically. The study traces Indonesia's regulatory evolution from the Consumer Protection Law 1999 (65% protection effectiveness) through financial sector-specific regulations to the 2023 Policy Guarantee Program (95% protection effectiveness). Analysis reveals four-tiered legal protection mechanisms: preventive (75% effectiveness through product transparency requirements), corrective (70% effectiveness via mediation and arbitration), repressive (80% effectiveness through administrative sanctions), and restorative (95% effectiveness via policy guarantee schemes). Findings indicate that payment uncertainty in unit-linked products stems from investment unit price volatility, operational complexity, and standard clause ambiguity, creating borderline cases requiring judicial interpretation. The research demonstrates that while Indonesia's regulatory framework has significantly evolved, practical implementation faces challenges in consumer education and claim standardization. The study concludes that restorative mechanisms through policy guarantee programs represent the most effective approach for systematic risk management, while complementary preventive, corrective, and repressive mechanisms remain essential for optimal legal certainty for BLife Plan MultiPro policyholders and similar investment-linked insurance products.